2016
DOI: 10.3389/fgene.2016.00191
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic DNA Methylation Profiling with MSRE: A Quantitative NGS Approach Using a Parkinson's Disease Test Case

Abstract: Epigenetics is a rapidly developing field focused on deciphering chemical fingerprints that accumulate on human genomes over time. As the nascent idea of precision medicine expands to encompass epigenetic signatures of diagnostic and prognostic relevance, there is a need for methodologies that provide high-throughput DNA methylation profiling measurements. Here we report a novel quantification methodology for computationally reconstructing site-specific CpG methylation status from next generation sequencing (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…6,7 Several studies have found differential methylation in SNCA and MAPT . 811 Furthermore, significant changes in DNA methylation were identified in multiple genes in both blood 10,12,13 and brain. 10 Relevant to the current study, dysregulation of Wnt signaling due to methylation was observed in the frontal cortex and midbrain sections of PD brains.…”
mentioning
confidence: 99%
“…6,7 Several studies have found differential methylation in SNCA and MAPT . 811 Furthermore, significant changes in DNA methylation were identified in multiple genes in both blood 10,12,13 and brain. 10 Relevant to the current study, dysregulation of Wnt signaling due to methylation was observed in the frontal cortex and midbrain sections of PD brains.…”
mentioning
confidence: 99%
“…DNA libraries were prepared from methyl-sensitive restriction endonuclease (MSRE) [ 30 , 31 ] fragmented genomic DNA (gDNA) using HpaII, which recognizes C (CpG) G sites. A standard sequencing protocol was then performed including randomized shearing (Covaris, Woburn, MA) and synthesis of a gDNA fragment library using Illumina TruSeq Nano library synthesis kits (San Diego, CA).…”
Section: Methodsmentioning
confidence: 99%
“…CpG methylation was calculated using a commercial bioinformatic pipeline to reconstruct probabilities of methylation at CpG sites (as used in Marsh and Pasqualone, 2014; Marsh et al., 2016; Crowgey et al., 2018; Genome Profiling LLC, Newark, DE). An overview of the pipeline workflow is available in Supplementary Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…Computational reconstruction of CpG methylation is based on a null selection model, where the distribution of m5C modifications at any single CpG site is expected to be 50% in a large population of cells (genome copies) for CpG sites that are non-functional or silent. Where CpG methylation status is important for cellular fitness and thus there is a selection force pushing the m5C distributions away from a 50:50 equilibrium, methylation of those CpG sites among all the cellular genome copies sampled can be measured (Marsh and Pasqualone, 2014; Marsh et al., 2016; Crowgey et al., 2018).…”
Section: Methodsmentioning
confidence: 99%